Method for preparing centimeter-level optical lens from sol-gel material and application of centimeter-level optical lens
By combining sol-gel materials with ultraviolet imprinting technology, centimeter-level optical lenses with high transmittance and weather resistance are prepared, which solves the problems of high cost, low production efficiency and poor material performance in traditional methods, and realizes the preparation of high-performance optical lenses with simple process and low energy consumption.
Patent Information
- Application Number
- CN202510186226.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-03-28
AI Technical Summary
Traditional optical lens preparation methods have problems such as high cost, low production efficiency and complex process. At the same time, liquid glass materials are easily brittle after curing, have poor unevenness and thermal stability, which affect their optical characteristics.
The sol-gel material is combined with ultraviolet imprinting technology, and the ultraviolet imprinting material is prepared by mixing MAPTMS, TMOS, MTMS and TPO in dilute hydrochloric acid, stirring and vacuum treatment, and high-performance optical lenses are obtained through ultraviolet curing and subsequent heat treatment.
It achieves high transmittance and good weather resistance of centimeter-level optical lenses, simple process and low energy consumption, and is suitable for a variety of environmental conditions.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer sol, and specifically relates to a method for preparing a centimeter-level optical lens with high transmittance and good weather resistance by using sol-gel material and an application thereof. Background Art
[0002] Optical lenses are widely used in many fields such as photography, optical instruments, medical equipment, military and defense. Traditional optical lens preparation methods such as precision compression molding, injection molding and ultra-precision machining technology are poor in the ability to prepare optical components with complex structures and multiple materials. At the same time, they are costly, inefficient and complex. UV imprinting technology is a new type of optical lens preparation technology. Compared with traditional preparation methods, it has significant advantages. First, it can obtain high-resolution graphics at the nanoscale, which is very useful for the preparation of high-precision optical components such as microlens arrays, diffraction optical elements, etc. At the same time, it does not require high temperature and high pressure conditions, and can achieve local irradiation curing.
[0003] The imprinting materials used in UV imprinting technology are mostly liquid glass as the main production material, and silica glass is obtained by degreasing and sintering at high temperature. However, liquid glass materials have disadvantages that cannot be ignored: the stirring time needs to be precisely controlled, and the material is prone to unevenness; after curing, it often shows high brittleness and is prone to cracking and peeling; during degreasing and sintering, its internal residual stress will cause defects in the structure; under certain environments, such as continuous ultraviolet radiation or temperature changes, its performance may gradually decline. The shortcomings of these materials, such as unevenness, brittleness caused by high cross-linking, poor thermal stability, and high shrinkage, have a great impact on optical properties and have certain limitations on their application. At the same time, since the degreasing and sintering step requires a higher temperature, usually reaching 1000℃-1200℃, the energy consumption is high.
[0004] The sol-gel method is to mix the raw materials (precursors) used in the liquid phase evenly, carry out hydrolysis and condensation chemical reactions, and form a low-viscosity solution. Therefore, molecular-level uniformity can be obtained in a very short time, and when the gel is formed, the reactants are evenly mixed at the molecular level. Compared with the preparation of liquid glass materials, the preparation of sol-gel materials is simple, while the processing of liquid glass materials is relatively complicated; sol-gel materials have relatively good thermal stability, good toughness, and are not easy to break, which makes them more reliable when subjected to mechanical stress or temperature changes. At the same time, compared with traditional high-temperature synthesis methods, the preparation of sol-gel materials is usually carried out at a relatively low temperature, and the heat treatment temperature is reduced to 200°C, which helps to reduce energy consumption and prevent undesirable phase changes or decomposition, maintaining the structure and properties of the material.
[0005] The present invention combines sol-gel materials with ultraviolet imprinting technology to prepare optical lenses. The whole process is easy to handle, and has the characteristics of simple process and low energy consumption. Therefore, it is of great significance to use sol-gel materials as ultraviolet imprinting technology materials to prepare centimeter-level optical elements. Summary of the invention
[0006] Purpose of the invention: The purpose of the present invention is to prepare centimeter-level optical elements using sol-gel materials. The use of sol-gel materials to prepare optical elements has low energy consumption and simple process.
[0007] Technical solution: The method for preparing centimeter-level optical lenses using sol-gel materials according to the present invention comprises the following steps: 3-(Isomethacryloyloxy)propyltrimethoxysilane (MAPTMS), tetramethoxysilane (TMOS), methyltrimethoxysilane (MTMS) and photoinitiator diphenyl (2, 4, 6-trimethylol) phosphine oxide (TPO) were mixed under acidic conditions provided by dilute hydrochloric acid to prepare sol-gel.
[0008] The mixture obtained in step (1) was stirred at 65°C and 150 kPa for 45 minutes, and then stirred at 95°C and 200 kPa for 15 minutes.
[0009] Furthermore, the mixture in step (2) is opened, and after vacuum treatment, dilute hydrochloric acid is added to the material again, and stirred until fully mixed to obtain the material required for UV embossing.
[0010] The polydimethylsiloxane precursor and the curing agent are mixed, stirred thoroughly, and allowed to stand until all bubbles disappear to obtain a PDMS colloid; The PDMS prepared in step (4) is molded onto a metal mold having the desired aspheric lens surface shape to obtain a soft mold for subsequent UV imprinting technology. At the same time, a layer of PDMS is spin-coated on a glass sheet as a mold cover.
[0011] After vacuum degassing, the UV imprinting material prepared in step (3) is poured into the mold, covered with a cover plate, and cured by double-sided UV light irradiation under a UV light source for a period of time to polymerize. The cured structure can replicate the desired shape from the surface of the PDMS mold.
[0012] The structure obtained in step (6) is placed at room temperature for 4-6 days, and then heated to 90° C. and kept warm for 1-2 days.
[0013] (8) The structure processed in step (7) is placed in a muffle furnace for sintering to obtain the desired structure.
[0014] Furthermore, in step (1), the molar ratio of MAPTMS:MTMS:TMOS:TPO is 1:5-6:1-2:0.16. Furthermore, the concentration of the dilute hydrochloric acid in step (1) is 0.5 mmol / L, and the mass of the added dilute hydrochloric acid accounts for 15.19 wt% of the total mass.
[0015] Furthermore, in step (3), the vacuum condition is -2×10 3 kPa negative pressure, and the mass of dilute hydrochloric acid added subsequently accounts for 0.5wt% of the total initial mass.
[0016] Furthermore, the optical density of the ultraviolet light source in step (6) is 4.5 mw / cm 2 , the light curing time is 2-4 minutes.
[0017] Furthermore, in step (8), the temperature is raised to 200° C. at a heating rate of 1° C. / min in a muffle furnace, and maintained at 200° C. for 1 h to obtain the desired structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Attached Figure 1 Schematic diagram of the prepared lens.
[0019] Attached Figure 2 Schematic diagram of a PDMS mold molded from a metal mold with the desired aspheric lens surface shape.
[0020] Attached Figure 3 This is the USAF 1951 resolution image captured by CCD for example 2.
[0021] Attached Figure 4 The USAF1951 resolution images captured by CCD for Example 3 and Example 4. DETAILED DESCRIPTION
[0022] The present invention will be further described below in conjunction with the embodiments. However, the scope of the present invention is not limited to the following embodiments. It will be appreciated by those skilled in the art that various changes and modifications may be made to the present invention without departing from the spirit and scope of the present invention.
[0023] Embodiment 1: A method for preparing centimeter-level optical lenses using sol-gel materials, comprising the following steps: (1) MAPTMS, MTMS, TMOS, and TPO were mixed in a molar ratio of 1:5.85:1.15:0.16 under acidic conditions provided by 0.5 mmol / L dilute hydrochloric acid to prepare a sol-gel.
[0024] (2) The mixture in step (1) was stirred at 65° C. and 150 kPa for 45 minutes under a closed condition, and then stirred at 95° C. and 200 kPa for 15 minutes.
[0025] (3) Further, the mixture in step (2) is opened to -2×10 3 After evacuating the material under a negative pressure of 0.5 kPa, 0.5 wt % of dilute hydrochloric acid based on the total initial mass was added to the material again, and the mixture was stirred until fully mixed to obtain a UV imprint material.
[0026] (4) mixing the polydimethylsiloxane precursor and the curing agent, stirring them thoroughly, and standing them until all bubbles disappear to obtain a PDMS colloid; (5) The PDMS prepared in step (4) is molded onto a metal mold having the desired aspheric lens surface shape to obtain a soft mold for subsequent UV imprinting technology. At the same time, a layer of PDMS is spin-coated on a glass sheet as a mold cover.
[0027] (6) The UV embossing material prepared in step (3) was vacuum degassed and poured into the mold, covered with a cover plate, and heated to an optical density of 4.5 mw / cm 2 The double-sided light curing was carried out under a UV light source for 2 minutes to polymerize. The cured structure can replicate the desired shape from the surface of the PDMS mold.
[0028] (7) The structure obtained in step (6) was placed at room temperature for 5 days, and then heated to 90° C. and kept warm for two days.
[0029] (8) The structure treated in step (7) is placed in a muffle furnace and heated to 200°C at a heating rate of 1°C / min, and then kept at 200°C for 1 h to obtain the desired structure.
[0030] Embodiment 2: A method for preparing centimeter-level optical lenses using sol-gel materials, comprising the following steps: (1) MAPTMS, MTMS, TMOS, and TPO were mixed in a molar ratio of 1:5.85:1.15:0.16 under acidic conditions provided by 0.5 mmol / L dilute hydrochloric acid to prepare a sol-gel.
[0031] (2) The mixture in step (1) was stirred at 65° C. and 150 kPa for 45 minutes under a closed condition, and then stirred at 95° C. and 200 kPa for 15 minutes.
[0032] (3) Further, the mixture in step (2) is opened to -2×10 3 After evacuating the material under a negative pressure of 0.5 kPa, 0.5 wt % of dilute hydrochloric acid based on the total initial mass was added to the material again, and the mixture was stirred until fully mixed to obtain a UV imprint material.
[0033] (4) mixing the polydimethylsiloxane precursor and the curing agent, stirring them thoroughly, and standing them until all bubbles disappear to obtain a PDMS colloid; (5) The PDMS prepared in step (4) is molded onto a metal mold having the desired aspheric lens surface shape to obtain a soft mold for subsequent UV imprinting technology. At the same time, a layer of PDMS is spin-coated on a glass sheet as a mold cover.
[0034] (6) The UV embossing material prepared in step (3) was vacuum degassed and poured into the mold, covered with a cover plate, and heated to an optical density of 4.5 mw / cm 2 The double-sided light curing was carried out under a UV light source for 2 minutes to polymerize. The cured structure can replicate the desired shape from the surface of the PDMS mold.
[0035] (7) The structure obtained in step (6) was placed at room temperature for 5 days, and then heated to 90° C. and kept warm for two days.
[0036] (8) The structure treated in step (7) is placed in a muffle furnace and heated to 200°C at a heating rate of 1°C / min, and then kept at 200°C for 1 h to obtain the desired structure.
[0037] (9) The prepared lens was immersed in solutions of pH = 1 and pH = 13 for two hours respectively.
[0038] After the lens prepared in this embodiment is treated with an acidic solution and a sodium hydroxide alkaline solution that is difficult for silicon dioxide materials to overcome, its imaging resolution remains consistent with that before the treatment. The USAF1951 resolution image generated by its CCD capture is shown in the attached figure. Figure 3 shown.
[0039] Embodiment 3, a method for preparing centimeter-level optical lenses using sol-gel materials, comprising the following steps: (1) MAPTMS, MTMS, TMOS, and TPO were mixed in a molar ratio of 1:5.85:1.15:0.16 under acidic conditions provided by 0.5 mmol / L dilute hydrochloric acid to prepare a sol-gel.
[0040] (2) The mixture in step (1) was stirred at 65° C. and 150 kPa for 45 minutes under a closed condition, and then stirred at 95° C. and 200 kPa for 15 minutes.
[0041] (3) Further, the mixture in step (2) is opened to -2×10 3After evacuating the material under a negative pressure of 0.5 kPa, 0.5 wt % of dilute hydrochloric acid based on the total initial mass was added to the material again, and the mixture was stirred until fully mixed to obtain a UV imprint material.
[0042] (4) Mixing the polydimethylsiloxane precursor and the curing agent, stirring them thoroughly, and letting them stand until all bubbles disappear to obtain a PDMS colloid.
[0043] (5) The PDMS prepared in step (4) is molded onto a metal mold having the desired aspheric lens surface shape to obtain a soft mold for subsequent UV imprinting technology. At the same time, a layer of PDMS is spin-coated on a glass sheet as a mold cover.
[0044] (6) The UV embossing material prepared in step (3) was vacuum degassed and poured into the mold, covered with a cover plate, and heated to an optical density of 4.5 mw / cm 2 The double-sided light curing was carried out under a UV light source for 2 minutes to polymerize. The cured structure can replicate the desired shape from the surface of the PDMS mold.
[0045] (7) The structure obtained in step (6) was placed at room temperature for 5 days, and then heated to 90° C. and kept warm for two days.
[0046] (8) Place the structure treated in step (7) in a muffle furnace and heat the temperature to 200°C at a heating rate of 1°C / min, and keep the temperature at 200°C for 1 h to obtain the desired structure.
[0047] (9) The prepared structure was placed in a sealed container, deionized water was dripped around it, and it was replenished every 4 hours to ensure a stable high humidity environment.
[0048] After heat treatment, the structure was tested to have a focal length of 13mm and a resolution of 28 lp / mm. Then the focal length and imaging resolution of the structure with different treatment times in a high humidity environment were tested. After analysis, it can be found that the focal length of the lens does not change with the increase of treatment time, and is stable at 13mm, while the imaging resolution is also stable at 28lp / mm. The resolution imaging is shown in the attached figure. Figure 4 As shown. It can be concluded that the optical properties of the lens prepared by UV embossing technology using sol-gel material are not affected by humidity.
[0049] Embodiment 4: A method for preparing centimeter-level optical lenses using sol-gel materials, comprising the following steps: (1) MAPTMS, MTMS, TMOS, and TPO were mixed in a molar ratio of 1:5.85:1.15:0.16 under acidic conditions provided by 0.5 mmol / L dilute hydrochloric acid to prepare a sol-gel.
[0050] (2) The mixture in step (1) was stirred at 65° C. and 150 kPa for 45 minutes under a closed condition, and then stirred at 95° C. and 200 kPa for 15 minutes.
[0051] (3) Further, the mixture in step (2) is opened to -2×10 3 After evacuating the material under a negative pressure of 0.5 kPa, 0.5 wt % of dilute hydrochloric acid based on the total initial mass was added to the material again, and the mixture was stirred until fully mixed to obtain a UV imprint material.
[0052] (4) mixing the polydimethylsiloxane precursor and the curing agent, stirring them thoroughly, and standing them until all bubbles disappear to obtain a PDMS colloid; (5) The PDMS prepared in step (4) is molded onto a metal mold having the desired aspheric lens surface shape to obtain a soft mold for subsequent UV imprinting technology. At the same time, a layer of PDMS is spin-coated on a glass sheet as a mold cover.
[0053] (6) The UV embossing material prepared in step (3) was vacuum degassed and poured into the mold, covered with a cover plate, and heated to an optical density of 4.5 mw / cm 2 The double-sided light curing was carried out under a UV light source for 2 minutes to polymerize. The cured structure can replicate the desired shape from the surface of the PDMS mold.
[0054] (7) The structure obtained in step (6) was placed at room temperature for 5 days, and then heated to 90° C. and kept warm for two days.
[0055] (8) The structure treated in step (7) is placed in a muffle furnace and heated to 200°C at a heating rate of 1°C / min, and then kept at 200°C for 1 h to obtain the desired structure.
[0056] (9) The lenses were stored at 0°C, 50°C, 100°C, and 150°C for 24 hours.
[0057] Characterize the focal length and imaging resolution of the lens (see attached Figure 4 After characterization, it was found that the focal length and imaging resolution of the lens remained the same as before treatment, regardless of whether it was in a low or high temperature environment.
[0058] The focal length and resolution of each embodiment are shown in Table 1 below.
[0059] Table 1 Focal length and resolution of specific embodiments.
[0060] Embodiment 1 Embodiment 2 Embodiment 3 Embodiment 4 focal length 13mm 13mm 13mm 13mm Resolution 28lp / mm 28lp / mm 28lp / mm 28lp / mm
[0061] In combination with the above embodiments, the focal length and imaging resolution of the lens in acidic environment, alkaline environment, high humidity environment, high temperature and low temperature remain the same as before treatment. The optical element prepared by sol-gel material has stable optical properties and strong weather resistance when humidity and temperature change drastically. Its high transmittance and strong weather resistance make it more widely used and have a longer service life.
[0062] Comparative Example 1: The difference from Example 1 is that in step (1), the molar ratio of MAPTMS, MTMS, TMOS and TPO is 1:5:2:0.16.
[0063] Comparative Example 2: The difference from Example 1 is that in step (1), the molar ratio of MAPTMS, MTMS, TMOS and TPO is 1:5.53:1.57:0.16.
[0064] Comparative Example 3: The difference from Example 1 is that the photocuring time in step (6) is 3 minutes.
[0065] Comparative Example 4: The difference from Example 1 is that the photocuring time in step (6) is 4 minutes.
[0066] Comparative Example 5: The difference from Example 1 is that in step (8), the temperature in the muffle furnace is raised to 150° C. at a heating rate of 1° C. / min, and the other experimental conditions are the same.
[0067] Comparative Example 6: The difference from Example 1 is that in step (8), the temperature in the muffle furnace is raised to 250° C. at a heating rate of 1° C. / min, and the other experimental conditions are the same.
[0068] By comparing Example 1 with Comparative Examples 1 and 2, it can be seen that when the proportion of MTMS is larger, the structure is more elastic. That is, when the molar ratio of MAPTMS, MTMS, TMOS, and TPO is 1:5.85:1.15:0.16, the toughness of the structure is optimal. By comparing Example 1 with Comparative Examples 3 and 4, it can be obtained that the longer the curing time, the sample tends to gradually turn yellow. By comparing Example 1 with Comparative Examples 5 and 6, it can be seen that the structure treated at 200°C and below can reach a transmittance of 87% within the visible light range, and a maximum of 91%. For samples treated at 200°C and below, as the heat treatment temperature increases, the moisture and alcohol content in the sample gradually decreases. The reduction in the content of water and alcohol in the sample is conducive to reducing its shrinkage rate and improving its weather resistance. The transmittance of the sample treated at 250°C is greatly reduced to only 71%. This is mainly because as the treatment temperature increases, some organic matter is pyrolyzed, resulting in a decrease in transmittance.
[0069] There is no public report on the preparation of centimeter-level optical lenses using sol-gel materials. The lenses prepared by this method have high transmittance and strong weather resistance; the preparation process has low energy consumption and simple subsequent treatment. Therefore, this method provides a new and feasible solution for the preparation of centimeter-level optical lenses.
Claims
1. A method for preparing centimeter-level optical lenses using sol-gel materials, comprising the following steps: (1) 3-(isomethylacryloyloxy)propyltrimethoxysilane (MAPTMS), tetramethoxysilane (TMOS), methyltrimethoxysilane (MTMS) and a photoinitiator diphenyl (2, 4, 6-trimethylol)phosphine oxide (TPO) were mixed under acidic conditions provided by dilute hydrochloric acid to prepare a sol-gel; (2) stirring the sol-gel in step (1) at 65°C and 150 kPa for 45 minutes, and then stirring at 95°C and 200 kPa for 15 minutes; (3) Further, after vacuum treatment of the sol-gel obtained in step (2), dilute hydrochloric acid is added to the material again, and stirred until fully mixed to obtain a UV imprint material; (4) mixing the polydimethylsiloxane precursor and the curing agent, stirring them thoroughly, and standing them until all bubbles disappear to obtain a PDMS colloid; (5) The PDMS colloid prepared in step (4) is molded onto a metal mold having a desired aspheric lens surface shape to obtain a soft mold for subsequent UV imprinting technology, and a layer of PDMS is spin-coated on a glass sheet as a mold cover; (6) After vacuum degassing, pour the UV imprinting material obtained in step (3) into the mold, cover it with a cover plate, and perform double-sided UV light irradiation curing under a UV light source. Continue irradiation for a period of time to polymerize. After curing, the structure can replicate the desired shape from the surface of the PDMS mold; (7) placing the structure obtained in step (6) at room temperature for 4-6 days, then heating it to 90° C. and keeping it there for 1-2 days; (8) The structure processed in step (7) is placed in a muffle furnace for sintering to obtain the desired structure.
2. The method for preparing centimeter-level optical lenses using sol-gel materials according to claim 1, characterized in that: The molar ratio of MAPTMS:MTMS:TMOS:TPO in step (1) is 1:5~6:1~2:0.
16.
3. The method for preparing centimeter-level optical lenses using sol-gel materials according to claim 1, characterized in that: The concentration of the diluted hydrochloric acid added in step (1) is 0.5 mmol / L, and the mass of the added diluted hydrochloric acid accounts for 15.19 wt % of the total mass of the solution.
4. The method for preparing centimeter-level optical lenses using sol-gel materials according to claim 1, characterized in that: The vacuum condition in step (3) is -2×10 3 kPa negative pressure.
5. The method for preparing centimeter-level optical lenses using sol-gel materials according to claim 1, characterized in that: The concentration of the diluted hydrochloric acid added again in step (3) is 0.5 mmol / L, and the mass accounts for 0.5 wt% of the total initial mass.
6. The method for preparing centimeter-level optical lenses using sol-gel materials according to claim 1, characterized in that: The optical density of the ultraviolet light source in step (6) is 4.5 mw / cm 2 , the light curing time is 2-4 minutes.
7. The method for preparing centimeter-level optical lenses using sol-gel materials according to claim 1, characterized in that: In step (8), the temperature is raised to 200° C. in a muffle furnace at a heating rate of 1° C. / min and kept at 200° C. for 1 hour to obtain the desired structure.